PMPD Perspective on Environment and Development - Chapagain, Prem Sagar (State, Society and Development: PMPD Perspectives, 2023)
People’s Multiparty Democracy (PMPD) is a creative thought of redefining Marxism in the twenty-first century. It advocates for multiparty competition, the rule of law, and supremacy through competition for leadership. It is also characterized by social justice, human rights, and economic equality. PMPD respects the embedded relationships between women and nature and internalizes the harmony between people and the environment for sustainable development. It acknowledges diversity and differences in society and environment, claiming that colonialism and neoliberalism have commodity nature and destroyed biodiversity, and displaced communities depending on natural resources. Further, it amplifies the access and control of resources to the local people and is utilized with the values as argued in Vedic philosophy, and utilizes the environmental resources with due recognition to the needs of future generations.